2022
DOI: 10.1111/gwao.12928
|View full text |Cite
|
Sign up to set email alerts
|

Passing as resistance through a Goffmanian approach: Normalized, defensive, strategic, and instrumental passing when LGBTQ+ individuals encounter institutions

Abstract: Passing and coming out are two divergent individual strategies historically associated with the LGBTQ+ community as they struggle to fit in with normative expectations at work and in life. While coming out has gradually become more common in organizations and national contexts that offer safeguards for LGBTQ+ individuals, passing remains an option where no such measures are available. Drawing on interviews with working-class LGBTQ+ individuals in a country with an adversarial context, that is, Turkey, we ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…Although atypicality can be seen as a positive quality, individuals may not reveal it until they achieve a leadership position. For instance, given that many LGBT+ workers report significant levels of discrimination and exclusion (Connell, 2010), LGBT+ leaders are less likely to come out before they take up leadership positions which provide them with relative security and safety (Özbilgin & Erbil, 2023; Özbilgin et al., 2023).…”
Section: Defining Authenticity and Atypicality In The Context Of Lead...mentioning
confidence: 99%
“…Although atypicality can be seen as a positive quality, individuals may not reveal it until they achieve a leadership position. For instance, given that many LGBT+ workers report significant levels of discrimination and exclusion (Connell, 2010), LGBT+ leaders are less likely to come out before they take up leadership positions which provide them with relative security and safety (Özbilgin & Erbil, 2023; Özbilgin et al., 2023).…”
Section: Defining Authenticity and Atypicality In The Context Of Lead...mentioning
confidence: 99%
“…Hence, men who attempt to present as heterosexual may be more motivated to eat meat. This need not apply solely to heterosexual men; in heteronormative culture, non-heterosexual men may at times feel pressure to present themselves as heterosexual (Ozbilgin et al, 2022).…”
Section: Masculine Norms Related To Men's Meat Consumptionmentioning
confidence: 99%
“…Despite numerous institutional interventions that aim to prevent sexual orientation and gender identity stigmatization and discrimination recently, it is a well-known fact that LGBTQ+ employees still encounter an unequal workplace experience in practice (Mara et al, 2021;Ozbilgin et al, 2022). One of the leading discriminations LGBTQ+ employees face in practice is the "gay glass ceiling effect" in which they report better managerial authority and supervisory skills, but they are not able to attain top managerial positions and even get paid less when compared to heterosexual individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Gender stereotypes related to heterosexist ideology also stand upon LGBTQ+ individuals to conform to assigned gender roles. Thus, LGBTQ+ employees may try to cope with the stigmatization and discrimination by trying to fit the social norms and they put much effort to close the gap between how they act and how they are expected to act (Ozbilgin et al, 2022). Previous research found that lesbian women perceived themselves as more masculine than bisexual and straight women (Kachel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%